2019
DOI: 10.1128/aac.01712-18
|View full text |Cite
|
Sign up to set email alerts
|

Patients at Risk for Aortic Rupture Often Exposed to Fluoroquinolones during Hospitalization

Abstract: Several studies have indicated that fluoroquinolone use may be associated with an increased risk of aortic aneurysm or dissection (AAD). Because patients with AAD or Marfan syndrome are at increased risk for aortic rupture, we performed a retrospective cohort study to determine the prevalence of systemic fluoroquinolone exposure and predictors of fluoroquinolone use in these patients. Data were obtained from the advisory board billing and administrative database, which contained information on 22 million adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…There have been recent warnings regarding the possible development of aortic aneurysms and dissection in patients at risk as antibiotic-class-related severe adverse events (100,101). In this line, mice challenged with a high-fat diet and a low-dose angiotensin infusion exposed to ciprofloxacin were more prone to developing aortic destruction and aneurysms (102).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been recent warnings regarding the possible development of aortic aneurysms and dissection in patients at risk as antibiotic-class-related severe adverse events (100,101). In this line, mice challenged with a high-fat diet and a low-dose angiotensin infusion exposed to ciprofloxacin were more prone to developing aortic destruction and aneurysms (102).…”
Section: Figmentioning
confidence: 99%
“…In this line, a curious phenomenon of paradoxical bacterial survival has been described in the presence of extremely high levels of (45,87,88,90,101,461). In several cases, these findings have led to the discontinuation of research, withdrawal from clinical practice, and strong restrictions to specific nonsystemic applications (such as topical or ophthalmic), to serious life-or limb-threatening infections, or to last-resort applications, such as compassionate use of several of these quinolones (45,100,454,462,463). Note that these regulations may differ among different countries.…”
Section: Quinolone Resistance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that ciprofloxacin could inhibit collagen production in tenocytes [25,26]. Another study suggested that patients with aortic aneurysm, aortic dissection or Marfan syndrome had a higher risk for aortic rupture when exposed to fluoroquinolones [27]. Moreover, compared with intravenous fluoroquinolones, oral fluoroquinolones carried a higher risk of negative effects, and levofloxacin was associated with not only aortic aneurysm but also aortic dissection [28].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…[25,26] Another study suggested that patients with aortic aneurysm, aortic dissection or Marfan syndrome had a higher risk for aortic rupture when exposed to fluoroquinolones. [27] Moreover, compared with intravenous fluoroquinolones, oral fluoroquinolones carried a higher risk of negative effects, and levofloxacin was associated with not only aortic aneurysm but also aortic dissection. [28] Based on these findings, future studies should focus on age stratification, the evaluation of individuals' fluoroquinolone with regard to the risk of aortic aneurysm or dissection and different exposure times, which may provide additional information because aortic diseases are rare adverse events that cannot be studied in randomized controlled trials.…”
Section: Implications For Clinical Practicementioning
confidence: 99%